2018
DOI: 10.1016/j.bja.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative structure and process quality and safety indicators: a systematic review

Abstract: CRD4201501277.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 125 publications
0
42
0
5
Order By: Relevance
“…A large number of process measures were identified in the perioperative indicators systematic review, but again, many lacked the high levels of evidence (Chazapis et al, 2018). Process measures are good targets for quality improvement, but it is important for this that they have a direct association with patient-centred outcomes (Boney et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of process measures were identified in the perioperative indicators systematic review, but again, many lacked the high levels of evidence (Chazapis et al, 2018). Process measures are good targets for quality improvement, but it is important for this that they have a direct association with patient-centred outcomes (Boney et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of perioperative process and structure indicators has recently evaluated both research and grey literature databases as well as professional and governmental body publications (Chazapis et al, 2018). This comprehensive review, covering an 11-year period (January 2005-January 2016), identified 1282 clinical indicators, which mainly focused on effectiveness (38%), safety (29%) and efficiency (26%).…”
Section: Introductionmentioning
confidence: 99%
“…It is wrong to assume that all systems and technologies used in high-income settings will lead to improvements elsewhere; however, availability of data from LMICs demonstrating a relationship between poor outcomes and lack of resources (e.g. critical care beds or availability of basic monitors, such as pulse oximetry and capnography) 9 might further support efforts to address these issues. This is particularly important when considering the competition for limited public finances that exist in Africa and similar settings.…”
Section: Reasons For Developing Risk Calculatorsmentioning
confidence: 99%
“…Thus, the question is whether we should continue to rely only on reading a label, or take the view that the instances where coloured labels prevent mistakes will outweigh those when colour might predispose to other problems. This illustrates the complex adaptive nature of safety interventionsdhow humans and systems change, sometimes unpredictablydin response to one another, and can lead to safety paradoxes, 9 in which our defences can themselves cause unanticipated…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…1 Improvement work goes largely unevaluated, says Dixon-Woods, citing a study that found 1282 quality indicators for the entire surgical pathway in the NHS, most of which had no or little evidence behind them. 2 "People pluck them out of the air and use them," says Dixon-Woods. "It's a problem for research because it's very difficult to compare one study with the next.…”
Section: Evidence For the Nhsmentioning
confidence: 99%